Gamelan Gong Suling for the Millennial Generation with Meguru Kuping Technique | Pembelajaran Gamelan Gong Suling Pada Generasi Milenial dengan Teknik Meguru Kuping - Putra, I Putu Agus Adi (Pusat Penerbitan LPPMPP ISI Denpasar, 2024)
Institut Seni Indonesia Denpasar has committed to implementing the Real Work Lecture program to foster empathy and concern for various societal issues while enhancing the community's quality of life and well-being. This initiative is designed to address current societal challenges, cultivate a deeper cultural understanding, and strengthen the character of the millennial generation. By doing so, ISI Denpasar aims to empower them to preserve and pass on cultural heritage amidst the rapid changes brought about by the digital era. Through these efforts, a concept emerged to develop community service projects organized by ISI Denpasar, with a primary focus on nurturing and refining the musical sensibilities of the millennial generation. One proposed strategy involves utilizing the traditional gamelan Gong Suling as a medium to engage and inspire young individuals to appreciate and continue cultural traditions. This approach enriches their cultural experiences and equips them with valuable skills and perspectives needed to navigate and contribute meaningfully to contemporary society. ISI Denpasar believes that by fostering a strong sense of cultural identity and responsibility among millennials through programs like the Real Work Lecture and community service initiatives, they can effectively bridge the gap between tradition and modernity, ensuring the enduring relevance and vitality of Indonesia's rich cultural heritage.